Smart Vehicle Spaces - , K. Venkatesh Prasad; Hodges, Steve; Noble, Brian (IEEE Pervasive Computing Magazine, 2016)
During the past few decades, cars have transformed from being relatively mundane spaces underpinned by mechanical platforms with sprinklings of electronics into complex computational platforms. As a result of this continual development and the smart spaces it has enabled, we are now seeing the signs of tectonic shifts in car-related experiences, ranging from ride services to autonomous vehicles. These are underpinned by the key elements of intelligent systems—sensing, actuation, computation and communication resources—which are now routinely built-in to cars, along with additional resources brought in via mobile devices and beamed-in from the cloud. This special issue offers an insight into what we can expect from smart vehicle spaces and the technology that enables them.